Inter Olhares: proposta de concepção de uma revista digital para abordar questões que afetam o cotidiano da UFPA - MATTA, Julia Marina Quemel (Universidade Federal do Pará, 2021)
Universities are great spaces for training human resources and producing knowledge, however, they also present issues that need to be faced and discussed with the academic community, such as violence, prejudice or waste disposal, among others that are also evident in society in general. It is understood that these issues are not always widely discussed within the scope of formal education and, based on this principle, in the context of the Federal University of Pará (UFPA), this work has as its general objective the dissemination and circulation of studies related to problems that involve the everyday life of the University, like the overpopulation of dogs, seeking to promote a wide circulation, awareness and debate about complex topics by the academic community, which requiresintegrated solutions. The specific objectives were proposed: (i) to identify what perceptions the academic community has about the subject treated in the first example of the magazine; (ii) designing a digital magazine to address UFPA's daily problems; and (iii) evaluate and validate a proposal. In this context, a digital magazine called "Inter Olhares" was created, aimed at everyone who transits and circulates in the Institution: students, teachers, technical-administrative servers, service providers. service and visitors. The magazine is structured in five sections: Perception, Fact, Complexity, Reflection and Attitude, with a proposal for semiannual periodicity and brings, in the first edition, the theme of stray dogs overpopulation in the Professor José da Silveira Netto University City, headquarters of UFPA, in Belém. In order to design the product, it was necessary to go through some steps that covered the method of analyzing the perception of problems at UFPA and collecting data in the community; a definition of the journal's prerequisites; structuring the editorial plan; the preparation of the first issue of the magazine; and the validation. As a result, it was found that a magazine, in general, can be used in the context of teaching, especially in the scope of non-formal education, due to its versatility, clarity of language and accessibility. The availability of the magazine in digital format, with the different resources offered, expands the magazine's accessories, especially because of the possibility of simplifying information and the combination of different media, which can increase the chances of learning the subjects used in editions.